2010
DOI: 10.1590/s1678-77572010000500003
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of the degree of conversion of resin-based luting cements

Abstract: ObjectiveThis study analyzed the degree of conversion (DC%) of four resin-based cements (All Ceram, Enforce, Rely X ARC and Variolink II) activated by two modes (chemical and dual), and evaluated the decrease of DC% in the dual mode promoted by the interposition of a 2.0-mm-thick IPS Empress 2 disc.Material and MethodsIn the chemical activation, the resin-based cements were prepared by mixing equal amounts of base and catalyst pastes. In the dual activation, after mixing, the cements were light-activated at 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 28 publications
2
35
1
18
Order By: Relevance
“…A similar method (with thin films of the individual pastes) has been described in the literature, but there was not much information on how the data was dealt with. 26 Furthermore, other studies comparing these two protocols were not found.…”
Section: Discussionmentioning
confidence: 99%
“…A similar method (with thin films of the individual pastes) has been described in the literature, but there was not much information on how the data was dealt with. 26 Furthermore, other studies comparing these two protocols were not found.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical longevity of these restorations is dependent of the cavity design, the indirect restorative material, the properties of the RC and cementation technique selected 9 . The most common tests for resin-ceramic bonding measurements are shear and tensile bond strength tests 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall properties of RC using the dual-cure system seem to be superior when compared to the single-cure system 19 . Noronha Filho et al 9 (2010) observed that RC present low degree of conversion when the indirect restoration material attenuates the light activation. The dual curing RC has been developed to overthrown these conditions 20 .…”
mentioning
confidence: 99%
“…Durante esse processo, as ligações duplas de carbono (C=C) existentes na porção alifática da cadeia são quebradas e convertidas em ligações covalentes (C-C) entre os monômeros metacrilatos, formando a cadeia polimérica (Noronha-Filho et al, 2010).…”
Section: Fatores Que Podem Interferir Na Polimerização Do Cimento Resunclassified
“…Estudos demonstraram que vários fatores podem interferir na eficácia da polimerização do cimento empregado na cimentação de restaurações indiretas em cerâmica ou resina composta: a composição, espessura, opacidade e a cor do material restaurador podem atenuar a passagem da fonte de luz e, consequentemente, diminuir a porcentagem de polimerização do cimento (Fonseca, 2004;Soares et al, 2006;Borges et al, 2008;Hickel, 2008;Meng et al, 2008;Pazin et al, 2008;Hooshmand et al, 2009, Noronha-Filho et al, 2010Valentino et al, 2010 O sucesso clínico de um procedimento restaurador indireto depende de inúmeros fatores e entre eles, a técnica de cimentação usada que cria um link entre a restauração e o dente (Radovic et al, 2008;Souza et al, 2011). Para a seleção de um agente de cimentação ideal, vários fatores devem ser considerados, incluindo suas propriedades físico-químicas, a técnica de uso e o planejamento clínico.…”
Section: Introductionunclassified